Serum immunoglobulin free light chains are sensitive biomarkers for monitoring disease activity and treatment response in primary Sjögren's syndrome. (2nd July 2018) - Verstappen, Gwenny M; Moerman, Rada V; van Nimwegen, Jolien F; van Ginkel, Martha S; Bijzet, Johan; Mossel, Esther; Vissink, Arjan; Hazenberg, Bouke P C; Arends, Suzanne; Kroese, Frans G M; Bootsma, Hendrika
Abstract: Objectives: Serum immunoglobulin free light chains (FLCs) are frequently elevated in B-cell-mediated autoimmune diseases, including primary SS (pSS). The objective of this study was to assess if serum FLCs can contribute to classification, mucosa-associated lymphoid tissue (MALT) lymphoma detection, monitoring of disease activity and treatment response in pSS. Methods: Serum samples of 100 consecutive patients suspected of pSS were included. Forty-five patients fulfilled ACR-EULAR criteria for pSS. Additionally, samples of 17 pSS patients with MALT lymphoma and longitudinal samples of pSS patients treated with rituximab ( n = 20), placebo ( n = 10) or abatacept ( n = 15) were included. Serum FLCκ/FLCλ was measured by nephelometry or turbidimetry. Results: At diagnosis, FLCκ and FLCλ serum levels were significantly higher in pSS compared with non-SS sicca patients. The FLCκ/FLCλ ratio was abnormal in 11% of pSS patients. In established MALT-pSS patients, without recent rituximab treatment ( n = 12), 50% had abnormal FLCκ/FLCλ ratios. FLC measurement had no additional value for pSS classification, compared with IgG and anti-SSA. FLC levels correlated significantly with systemic disease activity, assessed by EULAR SS Disease Activity Index (ESSDAI) and clinical ESSDAI, both cross-sectionally and longitudinally following treatment. Treatment with rituximab or abatacept significantly lowered FLC levels. FLCs show a large sensitivity to change and relative changes induced by treatment were higher compared with IgG. Conclusion: Serum FLCs are elevated in pSS, and abnormal FLCκ/FLCλ ratios may be indicative for the presence of MALT lymhoma. FLC levels can be used as a biomarker for systemic disease activity and monitoring treatment responses. FLCs are sensitive to change and have more favorable kinetics than IgG.